Relationship Between Postpartum Health Care With Contraceptive After Childbirth In Indonesia - Arantika Meidya Pratiwi (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2018)
Result of SDKI 2012 show that MMR in Indonesia is 359 deaths per 100,000 live births. This result show that Indonesia still far from the target SDGs (Suitable Development Goals), who reducing the Maternal Mortality Rate (MMR) to 70 per 100,000 live birth. One of the breakthrough programs of the Ministry of Health in an effort to accelerate the reduction in maternal mortality is to increase contraceptive after childbirth. The coverage of contraceptive after childbirth in Indonesia is still far from what is expected, from the 2013 Riskesdas data the coverage of contraceptive after childbirth in Indonesia was only 59.6%. Papua became a province with the lowest coverage of only 26%. The purpose of this study was to determine the relationship between postpartum health care and contraceptive after childbirth in Indonesia. This study using  secondary data from "2013 Basic Health Research" conducted by the Health Research and Development Institute. The 2013 Riskesdas survey uses a cross sectional design. The results of the Chi-Square test showed that there were 0,0001, which meant that there was a relationship between postpartum health care and contraceptive after childbirth in Indonesia. While the results of the analysis of OR values were 1.595, which means that mothers who received health care during the postpartum were 1.6 times more likely to use contraceptive after childbirth.